DIFFERENTIATION STRATEGY OF AGRIFOOD WITH IMPACT ON ECONOMIC AND SOCIAL DEVELOPMENT OF VULNERABLE POPULATIONS CASE STUDY OF COLLECTIVE TRADEMARK - Maria Ines Jatib; Diaz Cano Muncha; Marina Bentivegna (European Scientific Journal, ESJ, 2015)
The competitiveness development in agribusiness is based on implementing a valueadded and marketing strategy for the agrifood product that positions it into national and international market. Instruments related to Intellectual Property, in order to be included in the property’s right allows differentiation as an intangible asset, providing legal security and guaranteeing that the income generated by such differentiation get back to the farmers. In this case study referred to Rabbit production in the province of La Rioja, Argentina, collective trademark is the right tool to apply since it enables the construction of "social capital"; bringing together stakeholders around a production and marketing scheme, empowering them and transcending the economic´s aspects. The implementation of trademark’s strategy is reached after a process of knowledge’s construction that allows improvements with the use of existing technologies and resources that helps to increase scale’s economy, and the incorporation of entrepreneur’s associations. Those actions have been supported and driven by local development’s policies of the local government.